Professional attitude to patients' values in decision-making - Broggi, Marc Antoni (Psicooncología, 2010)
For the clinical decisions, every time an attitude different from needs on the part of the professionals which during long time has stayed. Now knowledge and abilities need to come near to the universe of each patient, because this one is decisive at the moment for the clinical decision making. We must be conscious of the lack of formation in this land and of the necessity to adopt an attitude that allows us to be to the height of which it is expected of our professionalism in our daily task. Thus, it is essential to know and to respect a series of new rights of the ill citizens and the new duties that, therefore, concern to us. But the aid to our patients cannot be limited to respect legally established; it must also include the aid to be able to exert these rights according to its changing necessities in a vulnerability state. Sometimes, it is necessary to help with loyalty to decide independently. This requires a curiosity towards the world of values of everyone, a hospitality to accept the newness that represents and an open dialogue that can arrive at shared decisions. For which all it is possible is necessary to know how to manage the clinical relation towards forms of frank deliberation warmer than those than an impatient patient and a scientist or cold civil employee settle down in a simple contract between. The clinical decisions depend on previous decisions of the professionals on these interpersonal aspects.